On the word bestseller in Polish: frequency, meaning, context of use - Zabawa, Marcin (Papers in Linguistics, 2022)
The aim of the present paper is to analyze the English borrowing bestseller used in Polish. The first part of the article provides a description of meanings and the frequency of use of the form bestseller in the source language, i.e. English; then, analysis of the frequency of use of the word bestseller in Polish is provided and definitions of the word available in Polish dictionaries are analyzed. The paper essentially focuses on discussing new contexts of use of the word in question, presented against the background of dictionary definitions (in both Polish and English dictionaries), and illustrated with numerous examples, taken primarily from the Internet. The article shows that although the word under scrutiny was initially used mainly with reference to books (and later also music and films), now it significantly expanded its scope and appears in various contexts, such as those connected with food in restaurants, hotel rooms or dance lessons. The final part of the article is devoted to normative assessment of the word bestseller in Polish: it does not pose any problems in connection with morphology, but it is not always the most appropriate form in a given context. It seems that sometimes marketing and advertising needs, rather than purely semantic ones, are given priority.